Clinical Practice Guidelines for Acute Pancreatitis Treatment. - Francisco García Valdés; Jorge Luis Ulloa Capestany; Reinaldo Jiménez Prendes; Rudis Miguel Monzón Rodríguez; Carlos Jaime Geroy Gómez (Medisur, 2009)
Clinical Practice Guidelines for Acute Pancreatitis Treatment. It is the acute inflammatory reaction of the pancreas, affecting a gland that was previously healthy and causes its self-digestion with variable complications of local and distal systems of organs. Its etiological agents, clinical presentation, diagnostic methods and therapy are described. It includes assessment guidelines focused on the most important aspects to be accomplished.